UPAYA PENCEGAHAN BULLYING MELALUI REPRESENTASI SERIAL ANIMASI NUSSA DAN RARA DI MADRASAH DINIYAH AWALIYAH SULLAMUL KHAIRIYAH DESA SERIMBU KABUPATEN LANDAK TAHUN AJARAN 2024/2025 - Winda Fitriyanti; Neneng Sulasmi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study is based on the importance of educational animation media in conveying moral messages and shaping children’s character from an early age, as exemplified by the animated series Nussa and Rara. The purpose of this research is to analyze the representation of bullying in the Nussa and Rara series and evaluate its impact on children’s understanding of bullying, particularly within the learning environment of Madrasah Diniyah Awaliyah Sullamul Khairiyah, Serimbu Village, Landak Regency. This study employs a qualitative approach with phenomenological method. Data were collected through observation of selected episodes related to the theme of bullying, as well as interviews with students as research subjects. Several episodes, including Stop Bullying, Jangan Menuduh, Maaf (Part 1 & 2), and Tolong dan Terima Kasih were chosen as the primary focus since they explicitly depict various forms of bullying and anti-bullying values. The findings reveal that after watching the series, children’s understanding of bullying significantly improved. They began to recognize that mocking, ignoring, and making accusations without evidence are unacceptable behaviors that can harm others emotionally and socially. The series not only represents acts of bullying but also offers solutions by modeling empathy, mutual respect, and the importance of apologizing. Thus, Nussa and Rara proves to be an effective educational medium in supporting character education and promoting early prevention of bullying.